STATE AND DEVELOPMENT EVALUATION OF PRODUCTION TECHNOLOGIES IN THE MANUFACTURING INDUSTRY - A. E. Miller; T. I. Reutova (Вестник СибАДИ)
Introduction. The methodology formation of the status and the development of the production technologies at the manufacturing industry enterprises of the Russian Federation in the context of priority scientific and technological development of the Russian economy are presented in the article. Materials and methods. The basic methodological approaches used for the research are the system and the process approaches, which are reflected in scientific and practical material of the general systems theory, also the theory of the organization and the technical and technological approaches.Results. The scientific development concept of the production technologies at the manufacturing industry enterprises is directed to the determination of the maintenance versatility and to the multidirectivity extension of the new technologies' implementation in domestic manufacturing industry within the development priorities of the Russian scientific and technical complex. Within the practical implementation ofthe production technologiesdevelopment concept the organizational business case capable model is proposed for providing the achievement of the technological orientation influence of the manufacturing industry enter prise and for the acceptable version of the organizational decision's choice. Conclusion. The main directions of the received results' usage would be the adjustment of the state programs' contents towards subprogrammes (sections) adding for modernization according to the new technological directions; the actions' separation directed to support the research in the digital and additive production sphere, the robotic technology and new production technologies would be implemented.